Hepatocellular carcinoma as extracolonic manifestation of Lynch syndrome indicates SEC63 as potential target gene in hepatocarcinogenesis - Casper, Markus; Weber, Susanne Nicole; Kloor, Matthias; Müllenbach, Roman; Grobholz, Rainer; Lammert, Frank; Zimmer, Vincent (Scandinavian journal of gastroenterology, 2013)
Objective. Lynch syndrome is a cancer predisposition syndrome caused by germline mutations in DNA mismatch repair (MMR) genes with microsatellite instability (MSI) as its molecular hallmark. Hepatocellular carcinoma (HCC) has not been considered part of the tumor spectrum. The aim was to provide a detailed molecular characterization of an HCC associated with Lynch Syndrome (Muir-Torre variant). Materials and methods. HCC samples were analyzed for MSI, MMR protein expression and coding microsatellite instability (cMSI). Since cMSI also affected SEC63 coding for an endoplasmic reticulum membrane protein with implications for intracellular protein translocation, its impact on hepatocyte growth control was assessed in an established short-term model. Recombinant inbred mouse lines (BXD) showing different basal SEC63 expression levels were treated with the chemocarcinogen diethylnitrosamine (DEN) intraperitoneally. Proliferation and apoptosis of hepatocytes were determined after 48 h using Ki67 and TUNEL assays. Results. The HCC was high-grade microsatellite unstable with loss of MSH2 expression. cMSI was detected in four genes (ASTE1, SEC63, TAF1B, TGFBR2). However, only TGFBR2 is known to be involved in hepatocarcinogenesis. When investigating the impact of SEC63 expression on hepatocyte growth control in the murine model, low hepatic expression correlated significantly (p < 0.05) with a decrease in apoptosis and increased proliferative activity. Conclusions. For the first time, an HCC with characteristic molecular features of association with Lynch syndrome is described. The pro-carcinogenic growth behavior of hepatocytes with low SEC63 expression in the murine model indicates a potential role for SEC63 in hepatocarcinogenesis in general, but this needs further functional validation.
Gesehen am 12.03.2021